Sanksi Kebiri Kimia Bagi Pemerkosa Anak perspektif Mashlahah Mursalah - Mashlahatul Azizah (Al-Jinayah: Jurnal Hukum Pidana Islam, 2017)
Abstract: This article analyses castration as punishment for underage rage from the perspective mashlahah mursalah. Chemical castration is introduced as one of punishment in rape with the victimof underage children based on article 81 of Government Regulation in Lieu of Law No. 1/2016. The Law was issued due to frequent occurrence of this kind of rape. The punishment was made severe to deter from its occurrence. Castration is in fact useful in preventing the vice. It has fulfilled requirements of mashlahah mursalah. Castration in the Government Regulation in Lieu of Law No. 1/2016 is subsidiary punishment. Cemichal castration in this punishment does not have permanent effect and applied only for certain offender and in application it is applied after undergoing main punishment coupled with rehabilitation under supervision of related government agencies, namely ministry of Law and human rights,ministry of social welfare and ministry ofhelath. By doing so, human rights remains protected and society will deemit useful Keywords: chemical castration, rape, mashlahah mursalah. Abstrak: Artikel ini membahas tentang analisis mashlahah mursalah terhadap kebiri kimia bagi pemerkosa anak. Adanya kebiri kimia dalam pidana pemerkosaan anak di bawah umur berdasarkan Pasal 81 Perppu No. 1 Tahun 2016. Hal tersebut disebabkan maraknya tindak kekerasan seksual terhadap anak, dan ancaman hukuman yang dimuat dalam Pasal 81 UU No. 35 Tahun 2014 belum menimbulkan efek jera kepada pelaku kekerasan seksual. Hukuman kebiri ini mengandung sebuah manfaat sebagaimana syarat-syarat mashlahah mursalah. Hukuman kebiri dalam Perppu No. 1 Tahun 2016 bersifat sebagai hukuman tambahan, tidak bersifat permanen, hanya diperuntukkan bagi pelaku yang masuk dalamkategori Pasal 76 D UU No. 35 Tahun 2014, dikecualikan bagi pelaku anak dan dalam pelaksanaanya dilakukan setelah pelaku menjalani pidana pokok dengan dibarengi adanya rehabiltasi di bawah pengawasan kementrian hukum, kementrian sosial dan kementrian kesehatan sehingga tidak menghapuskan hak asasi manusia dan adanya penambahan hukuman ini dapat menimbulkan suatu kemanfaatan di dalam kehidupan masyarakat. Kata Kunci: Kebiri kimia, pemerkosaan, mashlahah mursalah.